361 Prevalence and Trends of Surgical Intervention for Trigeminal Neuralgia in the Inpatient Setting in the United States: Analyses from a National Database from 2002-2015. (1st April 2022) - Alexander, Yohan; Alvi, Mohammed; Doherty, Ronan; Yolcu, Yagiz; Kerezoudis, Panagiotis; Brown, Desmond A.; Agarwal, Vijay; Van Gompel, Jamie J.; Ghogawala, Zoher; Link, Michael J.; Meyer, Fredric B.
Abstract : INTRODUCTION: Trigeminal neuralgia is a debilitating neurological condition characterized by sharp, stabbing pain in the distribution of the trigeminal nerve and its branches. For trigeminal neuralgia that is refractory to medical therapy, surgery is generally indicated. Herein, we sought to assess the prevalence of trigeminal neuralgia among inpatient admissions, utilization of surgical intervention, and trends of utilization of common surgical approaches for TN using a national database. METHODS: The National Inpatient Sample (NIS) was queried for all patients with trigeminal neuralgia using international classification of disease 9th revision clinical modification (ICD-9-CM) diagnosis code (350.1) between the 1st quarter of 2002 and the 3rd quarter of 2015. Cases were also classified into surgical groups using ICD-9 procedure codes which included MVD, percutaneous procedures and stereotactic radiosurgery. Using weighted discharge methodology, national estimates for prevalence, primary admissions, and utilization of each surgery type were computed. RESULTS: A total of 405, 445 patients with trigeminal neuralgia were identified between the 1st quarter of 2002 and the 3rd quarter of 2015. The inpatient prevalence of trigeminal neuralgia in this 14 year cohort was found to be 63.8 per 100, 000, and was found to increase from 54.9 per 100, 000 in 2002 to 76 per 100, 00 in 2015. A total of 67, 768 patients had a primary diagnosis of trigeminal neuralgia. Of these, 41, 473 (61.2%) underwent a surgical procedure; surgical utilization increased from 59.7% cases in 2002 to 69.1% in 2015. Of the cases undergoing a surgical intervention for trigeminal neuralgia, an MVD was performed for the majority of patients (87%, n=36, 083) followed by percutaneous procedures (7.3%, n=3, 036) and stereotactic radiosurgery (7.1%, n=2, 940). Furthermore, the percent-utilization of MVD among patients undergoing surgical intervention increased form 67.3% in 2002 to 98% in 2015, the percent utilization of percutaneous procedures fell from 17.9% to 2%, and the percent utilization of stereotactic radiosurgery fell from 15.5% to 0.4%. CONCLUSION: The trends within surgical management of trigeminal neuralgia have been rapidly evolving over the past two decades with a steady trend towards MVD.